Engineering Design and Five Whys–Based Analysis for Jig Redesign in a New Auto Press Pin Machine - Armijal Armijal; Muhammad Hamdan Fadhlani; Alfadhlani Alfadhlani; Prima Fithri; Reinny Patrisina (Andalasian International Journal of Applied Science, Engineering and Technology, 2026)
Abstract— PT ABC is a major automotive manufacturer in Indonesia producing NR-series and hybrid engines. To address limitations of the manual press pin machine, an auto press pin machine was developed. However, operational issues emerged during the load–unload process due to instability of the jig path, leading to workpiece misalignment and reduced process reliability. This study aims to identify the root causes of the jig path instability and propose an engineering-based improvement. Root cause analysis was conducted using the five whys method based on field observations and discussions with operators and technicians. The analysis indicated that geometric incompatibility between the jig track and the cylinder block was the primary cause of instability. Based on these findings, the jig path was redesigned using computer-aided design (CAD) with SolidWorks, followed by motion study simulations to evaluate stability and potential interference. The redesigned jig path demonstrated improved positional stability and smoother workpiece movement during simulation. Although quantitative performance indicators were not evaluated, the proposed design provides a technical foundation for future performance-based assessments